Analysis of the current classifier of types of purpose of agricultural lands and proposals for its improvement - Dorosh, Y.; Barvinskyi, A.; Ibatullin, Sh.; Dorosh, A.; Dorosh, О. (Land Management, Cadastre and Land Monitoring, 2021)
The analysis of the current Classification of types of intended purposes of land use is carried out. It is established that the existing 2-level Classification does not meet the modern requirements for monitoring land relations and the norms of current land legislation. The structure and content of the 4-level Classifier of typesof intended purposes of land use are proposed, which allows to determine in detail the type of permitted land use.It is established that the current classifier does not distinguish between the form of management and the type of land use. This issue is especially evident in the example of agricultural land, in which case the types of intended purposes indicate the legal form of landowner or user, rather than regulating the direct use of land. The proposed 4-level classifier is able to distinguish between the form of management and the type of land use.In forming this Classifier, the principles of complexity, systematicity, exhaustiveness, hierarchy and legality are taken into account; requirements of automated technologies for maintaining the State Land Cadastre and remote methods of land monitoring are considered, comprehensive and systematic methodological approaches in compliance with current domestic land legislation and relevant bylawsare applied; principles of openness and manufacturability, as well as recommendations of international organizationsare taken into account.Key words: agricultural lands, classifier, classes, types of purpose of land plots.